An ion-gating multinanochannel system based on a copper-responsive self-cleaving DNAzyme. Issue 65 (22nd July 2016) - Chen, Yang; Zhou, Di; Meng, Zheyi; Zhai, Jin
Abstract : An ion-gating nanochannel system was built by immobilizing a Cu 2+ -responsive self-cleaving DNAzyme, which could control the ion transport by regulating the surface charge density of the channels. Abstract : We developed an ion-gating nanochannel composite system by immobilizing a Cu 2+ -responsive self-cleaving DNAzyme into PET conical multinanochannels, which could control the ion transport by regulating the surface charge density of the channels.